Determinants of Students' Interest in Using BSI Cardless Withdrawal: Evidence from FEBI UINSU - Saibarani Nabila; Nurwani Nurwani; Laylan Syafina (Indonesian Journal of Islamic Economics and Finance, 2026)
Despite the growing adoption of digital banking services in Indonesia, empirical studies on the determinants of cardless withdrawal usage particularly within Islamic banking contexts remain limited. This study examines the influence of efficiency, convenience, and security on students’ interest in using the BSI Cardless Withdrawal feature, grounded in the Technology Acceptance Model (TAM). Using a quantitative survey approach, data were collected from 100 FEBI UINSU students selected through accidental sampling. Multiple linear regression analysis revealed that efficiency and security positively and significantly influenced students’ interest, while convenience did not yield a significant effect. Simultaneously, all three variables collectively had a significant positive impact. These findings contribute to the Islamic digital banking literature by highlighting that perceived security and operational efficiency are the primary drivers of cardless withdrawal adoption among young Muslim banking users, offering actionable insights for BSI in prioritizing service improvements.